Effect of Polyurethane Resin Additives on the Impact Toughness of Epoxy Resin Reinforced with woven roving Glass - Jawad, M. K. (Iraqi Journal of Physics, 2009)
I mpact strength for Epoxy/Polyurethane, Blends and their composites with twolayers of Glass fibers (0-90) are calculated.The impact strength of the blends and composites decrease with increasing weightby weisht percentage of polyurethane . This result is attributed to the high elasticityof PU , and to the immiscibility between the polymer blends as well as the fiberdelaminates